2017
DOI: 10.3892/mmr.2017.7607
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of long noncoding RNA AP003419.16 predicts high risk of aging-associated idiopathic pulmonary fibrosis

Abstract: Long noncoding RNAs (lncRNAs) are able to regulate adjacent genes and thus participate in the incidence in the present study has identified lncRNA AP003419.16, adjacent to the protein-coding gene ribosomal protein S6 kinase B-2 (RPS6KB2). RPS6KB2 is believed to be involved in the process of aging and idiopathic pulmonary fibrosis (IPF), due to its activation by growth factors and regulation by the protein kinase mTOR signaling pathway. The results of the present study indicated that the expression of AP003419.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…Recently, lncRNA AP003419.16 was reported to be involved in the IPF process, but its underlying working mechanism still needs to be elucidated. 15 This study is a follow-up to previous research conducted in our laboratory. Our previous study was the first to report the different lncRNA profiles in IPF.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, lncRNA AP003419.16 was reported to be involved in the IPF process, but its underlying working mechanism still needs to be elucidated. 15 This study is a follow-up to previous research conducted in our laboratory. Our previous study was the first to report the different lncRNA profiles in IPF.…”
Section: Introductionmentioning
confidence: 90%
“…Interestingly, lncITPF expression increased with age, which could be due to the fact that age is the strongest demographic risk factor for IPF. Hao et al 15 also reported that lncRNA AP003419.16 regulates its adjacent gene RPS6KB2, which is involved in the process of aging and IPF. These findings are beneficial in determining whether the abnormal lncITPF can be taken as a biomarker or a therapeutic target for IPF.…”
Section: Several Lncrnas Have Been Discovered Through High-throughputmentioning
confidence: 99%
“…Adhesion regulating molecule 1 (Adrm1) encodes the integral plasma membrane protein involved in proteolysis and deubiquitination [2730]. It has been reported that Adrm1 is downregulated in ageing-associated idiopathic pulmonary fibrosis [31]. Furthermore, downregulation of Adrm1 at the mRNA and protein levels leads to slower wound-healing [32].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of lncRNA AP003419.16 and its adjacent gene RPS6KB2, increased significantly in patients with IPF. More importantly, AP003419.16 might increase the possibility of aging-associated IPF [13]. The lncRNA, CDKN2B-AS1, appears down-regulated in IPF patients compared with healthy controls.…”
Section: Lncrnas Can Regulate Target or Adjacent Gene In Ipfmentioning
confidence: 99%